Climatic and environmental influences on mountain pine (Pinus montana Miller) growth in the Central Italian Alps - M. PELFINI; G. LEONELLI; M. SANTILLI (INSTITUTE OF ARCTIC AND ALPINE RESEARCH, 2006)
In this paper we analyze upright mountain pine (Pinus montana Miller) radial growth responses to climatic and environmental factors in a valley of the Central Italian Alps. This valley is characterized by intense geomorphological dynamics that can mostly be traced back to instability processes and particularly to debris flows. Here, there are also less active areas that allow undisturbed tree growth and permit dendroclimatic research to be performed. The relationship between climatic factors and radial growth in mountain pine was established by Pearson's correlation and response functions using four chronologies. Two were built using trees located on opposite valley slopes; the other two from the valley bottom. One of these last two is constructed with trees growing in areas occasionally affected by sheetfloods. We found that the climate of the summer months has the strongest influence on tree-ring growth: especially May and July mean temperatures and June precipitation. In contrast, the chronology built with trees located in the valley bottom in an area affected by sheetfloods, shows different climate-growth relationships especially concerning summer precipitation. The burial made by silt layers and the more impermeable conditions of the substrate seem to be the main factors regulating tree growth in this area. Comparing this chronology with the reference chronologies, we found that some years with growth anomalies in the disturbed site correspond to debris flow events dated by previous studies in nearby fans. This paper points out the potential use of mountain pine for dendroclimatic reconstruction and the influence of soft slope processes on tree growth.